Curriculum Implementation in Improving the Quality of Graduates at SMA Muhammadiyah 1 Palembang - Suroso; Sayid Habiburrahman; Hoirul Amri (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The curriculum is a comprehensive, holistic, methodical and collaborative curriculum management system. One way to optimise the curriculum is with curriculum management to oversee the policies of an education system, especially in Muhammadiyah Schools. The purpose of this study is to examine how curriculum management in Muhammadiyah schools can improve the quality of graduates. This research examines the synchronisation function of management in educational settings using qualitative methodology and descriptive analysis techniques. The type of data comes from primary data in the form of words or speech from informants, and secondary data in the form of documentation either from school documents, photos or recordings. Data were collected through observation, interviews and documentation. The data collected was then analysed with descriptive analysis that provides a detailed description of the phenomena observed. The research findings show that improving the quality of graduates largely depends on efficient planning, coordination, mobilisation, supervision and empowerment of resources. It has been proven that effective curriculum management can achieve the required quality criteria and promote a good teaching and learning environment. To achieve higher graduate quality, this study offers suggestions for implementing better curriculum management.